Surgical teams' attitudes and opinions towards the safety of surgical procedures in public hospitals in the Brazilian Federal District. (December 2016) - Santana, Heiko; Rodrigues, Maria; Socorro Nantua Evangelista, Maria
Abstract Background According to the World Health Organization, the WHO surgical safety checklist can prevent complications, improve communication and contribute to postsurgical safety culture; hence, there is a need to investigate the attitudes and opinions of surgical teams regarding safety utilizing the WHO instrument. The aim of this study was to assess the attitudes and opinions towards surgical safety among operating room professionals in three public hospitals in the Brazilian Federal District. Methods A cross-sectional study was conducted with the use of a checklist based on the safety attitudes questionnaire-operating room, sent out during the pre- and post-intervention surveys of the WHO surgical safety checklist (period I and period II) between 2012 and 2014. Results About 470 professionals, mostly nurse technicians, responded to the questionnaire in both periods. Regarding the perception of safety and agreement about the collaboration of the operating team, a significant statistical improvement of the nursing staff and anesthesiologists was observed in the operating room after the checklist was implemented. After utilizing the checklist before each surgical procedure, concerns about patient safety and compliance with standards as well as rules and hand-washing practices in the operating room statistically improved after the post-intervention, especially by the nursing staff. The checklist was considered easy and quick to use by most respondents. They also believed that the checklist inclusion improved communication, reflecting significant differences. At least 90.0 % of respondents from each team agreed that the checklist helps prevent errors in the operating room. Conclusions The study results showed progress in relation to the attitudes and opinions regarding surgical safety from operating teams in relation to the checklist response in the surveyed units. However, difficulties in its implementation are experienced, especially in relation to checklist use acceptance by the surgeons. New studies are needed to verify the sustainability of the surgical teams' changes in attitudes in the hospitals studied.